PENGELOLAAN KELAS DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS VIII SMP NEGERI 3 KARAWANG BARAT - Ikhsan Sayuti; Amirudin Amirudin; Iqbal Amar Muzaki (Universitas Negeri Medan, 2023)
Islamic education is currently provided in a classroom setting in SMP Negeri 3 West Karawang's eighth grade. In addition to data analysis utilizing the Miles and Huberman Models, the aim of this study is to ascertain how PAI instructors in class VIII at SMP Negeri 3 Karawang Barat use classroom management strategies. The study's findings demonstrate that a permissive strategy is utilized to regulate classrooms. Positive punishment is used to coach children in class VIII in behavior management, and individual and group issues frequently cause learning barriers. Additionally, the teacher's remedies involve fostering a peaceful environment in the classroom.